وحدة القصيدة في منهاج) حازم القرطاجني - د آدم محمد أبو القاسم عبد الله; د/أحمدعثمانفضيلحسن (White Nile Journal for Studies and Research, 2014)
the study aims to reveal the role of for the Hazim Elgortigani to comprehend the pattern for the traditional poem unity and hoe he benefited from accumulation of the latest Arab scholars knowledge besides what they got from Aristotle's efforts on the text unity. In fact the scholars a Hempted a lot to create a sense for the poem unity. The study reveals that Hazim in tented to integrative unity planning this unity hadn't been achieved as an integrated unity like the other linguistic arts. The study also showed that Hazim intended to plan for this unity in a hieradical way that depended on ppsychlogical and moral base in addition to stylistic. orgnizational and artiste way so as to gather all these traits in order to create the following of unity. To Hazim's contexts for experimentation.